The Effect Of Task-Oriented Gait Training Program On Improve The Walk Ability In Post Stroke Patients - Nurul Halimah; Sartoyo Sartoyo; Achmad Fariz (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2022)
Stroke is the main cause of disability and death in the world, which can make sufferers experience a decrease in quality of life, such as common problems from stroke are balance disorders, endurance, walking speed, cognitive function and walking ability. This study aims to determine the effect of task-oriented gait. training on changes in balance, endurance, walking speed, cognitive function and the ability to walk in post stroke patients. This research is a quasy experimental research with a pre-test-post-test two group design approach. This study evaluated the balance, endurance, walking speed, cognitive function and walking ability of post-stroke patients. This research was conducted at RSKD South Sulawesi (Stroke Center) Makassar and RSUD Haji Makassar with a total sample of 15 patients aged 40 years and over, diagnosed with post stroke movement function disorders, confirmed medical records that were scheduled to undergo physiotherapy. Samples were taken using purposive sampling method. Balance is measured by the Berg Balance Scale (BBS), endurance is measured by a 6-minute Walk Test (6MWT), walking speed is measured by a 4-meter Timed Walk (Gait Speed Test), and walking ability is measured by Modified Functional Ambulation Categories (mFAC). Measurements were made before the intervention and after the treatment group and the control group. The results of the intervention group study showed that Task-Oriented Gait Training gave significantly better resultsthan the control group.